(untitled) (Colombia Medica, 2024)
Assuming leadership from an ethical stance with responsibility for action proposes a complex challenge to achieve, because of the many aspects inherent to human beings and their evolutionary processes. It is necessary to undertake ways and ventures to weave forms and experiences that lead to it. The School of Nursing at Universidad del Valle, interpreting the university mission and based on its 2005-2015 Strategic Plan, assumes the responsibility of promoting opportunities and initiatives that foster leadership in students through the development of two strategies: promotion of Leadership and Training, through accompanying initiatives and representations of the Nursing Program students. This article describes different voices of students who have been participating in initiatives generated from the Leadership Project and the development of their strategies to recover and reveal the richness of its possibilities, as well as the difficulties of mobilizing a proposal involving democratic and humanist views on various forms of individual life and projected onto the horizon of the collective. Final reflection: The experience at the School of Nursing at Universidad del Valle about leadership and student participation provides the necessity to promote leadership based on the collective, but focusing on individual potential, as well as the personal and professional growth of students and teachers, which requires the conjunction of human, economic, academic and administrative efforts.